A comprehensive examination of exclusive breastfeeding through Quranic and Hadith perspectives alongside scientific insights - Md. Rasip, Zaifuddin; Hamzah, Amer Hudhaifah; Ibrahim, Haslina; Abdullah@Tan Ai Pao, Nur A’thiroh Masyaa’il Tan (HRMARS, 2024)
This article delves into the importance and benefits of exclusive breastfeeding (EBF) in Islam, as supported by the Quran and Hadith, while also analyzing its advantages through religious and scientific perspectives. EBF entails feeding infants solely breast milk for the first six months. Research highlights the remarkable advantages of EBF in enhancing the health of both infants and mothers, from both religious and scientific viewpoints. The positive impact of EBF on infant growth is highlighted, emphasizing its crucial role in providing essential nutrients for brain and immune system development. Additionally, EBF provides immunization protection through antibodies in breast milk and fosters a strong emotional bond between mother and infant, potentially enhancing emotional intelligence. Beyond immediate benefits, EBF acts as a preventive measure against chronic diseases in adulthood. Recognized as a crucial strategy for optimal infant growth, EBF yields lasting positive effects on long-term health and well-being. The forthcoming research will adopt a qualitative approach through an extensive literature review to appraise the importance of breastfeeding in infant development and scrutinize scientific revelations on its advantages, conducting comprehensive literature reviews of Islamic and scientific sources to assess breastfeeding's significance and benefits. Data will be extracted from various written sources, including the Quran, Hadith, books, journals, reports, and newspapers. The study's results are vital for offering in-depth insights to the community, promoting awareness of breastfeeding benefits, and encouraging a commitment to adopting breastfeeding practices for the benefit of their offspring. Furthermore, this article proposes several further research avenues to deepen our understanding of exclusive breastfeeding, including investigations into the influence of social and cultural environments on breastfeeding practices, as well as studies on strategies to enhance community awareness and support for exclusive breastfeeding. Thus, this article integrates religious and scientific perspectives to enrich the understanding of exclusive breastfeeding in Islam.